Clarifying the Relation between Social Interaction Anxiety and Cannabis Use: Personality as a Distinguishing Factor. (15th October 2019) - Rahm-Knigge, Ryan L.; Prince, Mark A.; Conner, Bradley T.
Abstract: Background: Individuals with social interaction anxiety, a facet of social anxiety disorder, are heterogeneous with respect to approaching or avoiding risky behaviors, including substance use. Additionally, the relation between social anxiety and cannabis use frequency has been inconsistent in the literature. Objective: The present study aimed to clarify the relation between social interaction anxiety and cannabis use by examining the effects of personality traits known to differentially predict substance use, including sensation seeking, emotion dysregulation, urgency, behavioral approach, and behavioral inhibition. Methods: We explored heterogeneity in social interaction anxiety using finite mixture modeling to discern profiles differing in mean scores on measures of social interaction anxiety and personality. We then examined how profiles differed in their likelihood of cannabis use. Results: The profile with low social interaction anxiety and high scores on personality measures was the most likely to use cannabis at all time periods. Two profiles with high social interaction anxiety scores were discerned. Between these two profiles, the profile with the highest levels of social interaction anxiety and most measured personality traits was more likely to use cannabis across all measured time periods. The profile with the high social interaction anxiety and low scores on personality measures was the least likely to use cannabis. Conclusions: Results of the present study identified personality traits most associated with increased risk of cannabis use for people high and low in social interaction anxiety, including facets of emotion regulation, urgency, and sensation seeking.